Halal Industry Transformation in the Era of Globalization: Uniting Local Values in the Global Market - Haq, Saipul (Fast in Social Sciences, 2025)
This article discusses the transformation of Indonesia's halal industry in the face of the challenges and opportunities of globalization, emphasizing the importance of integrating local values as a competitive strength. Amid the growing global demand for halal products, Indonesia holds a strategic position as the country with the largest Muslim population in the world. However, Indonesia's halal industry competitiveness is still limited by the dominance of regulatory approaches and weak innovation based on culture. This study uses a descriptive qualitative method with a literature review and case study approach, such as small-medium enterprises (SMEs) producing herbal medicine in Pasuruan and the Peh-Preneur community in Kediri. The findings indicate that local wisdom such as mutual cooperation, sustainability, and honesty in production can be a distinguishing element in branding halal products that align with global consumer trends. Furthermore, digitalization plays a crucial role in boosting visibility and market penetration for products based on local values. This article recommends that government policies prioritize local values in halal certification programs and encourage industry players to leverage cultural narratives in product and marketing strategies. The integration of regulation, innovation, and local wisdom is expected to create an inclusive halal industry ecosystem that is highly competitive and deeply rooted in the nation's identity amid a homogeneous global market.